Study of Phosphate Fertilizer Dosage and Boron Trioxide Fertilizer Concentration on Soybean Seed Yield and Quality (Glycine max [L.] Merill): Kajian Dosis Pupuk Fosfat dan Konsentrasi Pupuk Boron Trioksida Terhadap Hasil dan Mutu Benih Kedelai (Glycine max [L.] Merill) - Muhammad Pambudi; Priyono; Siswadi (Universitas Merdeka Madiun, 2024)
Soybean production in Indonesia is very fluctuating and tends to decline. The availability of quality soybean seeds is a problem being faced today. Phosphorus is a nutrient that plays a role in the formation of fruits and seeds. Boron is a nutrient that is involved in the germination of pollen and the formation of seeds. The aim of this research is to determine the effect of phosphate and boron fertilizers on the yield and quality of soybean seeds. This research was conducted from October 2023 to March 2024 at the Horticultural Seed Garden in Tohudan, Colomadu District, Karanganyar Regency, and the Plant Production Laboratory, Faculty of Agriculture, Slamet Riyadi University Surakarta. The research design uses a Completely Randomized Block Design (CRBD) where the first factor is phosphate fertilizer and the second factor is boron fertilizer. The conclusion of this study is that phosphate fertilizer at doses between 100 kg ha-1 and 200 kg ha-1 yields the best results for flowering time (34.42 days after planting), number of filled pods (106.00 pods), number of pods per plant (109.64 pods), and number of seeds per pod (2.64 seeds). Boron fertilization at a concentration of 0.29 g L-1 also provides the best results for flowering time (34.08 days after planting), number of filled pods (105.96 pods), number of pods per plant (108.47 pods), and number of seeds per pod (2.58 seeds). There is an interaction between boron and phosphate fertilization regarding the number of pods per plant and the number of seeds per pod. Phosphate and boron fertilization did not affect the weight of 100 seeds, germination rate, vigor index, and seed growth rate. Produksi kedelai di Indonesia sangat fluktuatif bahkan cenderung menurun. Ketersediaan benih kedelai bermutu menjadi permasalahan yang dihadapi saat ini. Fosfat merupakan unsur hara yang berfungsi dalam pembentukan buah dan biji-bijian. Boron merupakan unsur hara yang berperan dalam pembentukan perkecambahan serbuk sari dan pembentukan biji. Tujuan dari penelitian ini adalah untuk mengetahui pengaruh pupuk fosfat dan boron terhadap hasil dan mutu benih kedelai. Penelitian ini dilaksanakan pada bulan Oktober 2023 hingga Maret 2024 di Kebun Benih Hortikultura Tohudan, Kecamatan Colomadu, Kabupaten Karanganyar dan Laboratorium Produksi Tanaman, Fakultas Pertanian, Universitas Slamet Riyadi Surakarta. Rancangan penelitian menggunakan Rancangan Acak Kelompok Lengkap (RAKL) dimana faktor pertama adalah pupuk fosfat dan faktor kedua adalah pupuk boron. Kesimpulan dari penelitian ini adalah pupuk fosfat pada dosis antara 100 kg ha-1 – 200 kg ha-1 memberikan hasil terbaik terhadap waktu berbunga (34.42 HST), jumlah polong bernas (106.00 polong), jumlah polong per tanaman (109.64 polong), dan jumlah biji per polong (2.64 butir). Pemupukan boron dengan konsentrasi 0.29 g L-1 memberikan hasil terbaik terhadap waktu berbunga (34.08 HST), jumlah polong bernas (105.96 polong), jumlah polong per tanaman (108.47 polong), dan jumlah biji per polong (2.58 butir). Terdapat interaksi antara pemupukan boron dan fosfat terhadap jumlah polong per tanaman dan jumlah biji per polong. Pemupukan fosfat dan boron tidak berpengaruh terhadap bobot 100 butir, daya berkecambah, indeks vigor, dan kecepatan tumbuh benih.